Significant influencing factors and practical solutions in improvement of clinical nursing services: a Delphi study - Sarieh Poortaghi; Abbas Ebadi; Mahvash Salsali; Afsaneh Raiesifar; Nayyereh Davoudi; Nima Pourgholamamiji (BMC, 2019)
Abstract Background Clinical services evaluation with specific indicators are very helpful to identify improvable points. This study was conducted to analyze the factors affecting the quality of clinical nursing services and offer practical solutions for accreditation of clinical nursing services. Methods The present study was conducted using Delphi method with two rounds. At the beginning of the study a questionnaire was prepared using results of another project (clinical nursing services audit). This questionnaire was sent to 47 nursing and accreditation professionals. After the first round, causes and solutions were categorized. Then participants were asked to comment on the significance of each strategy on the prepared questionnaire. Results In the first round of Delphi in response to the question about the main causes and solutions of low quality of nursing clinical services, 394 causes and 212 solutions were mentioned by the participants. In the second round, considering moralists and specialization in the selection of nursing managers, staffing according to workload and attendance in comprehensive exam after graduation and before entering clinical fields attained the most importance. Conclusion Mismatch of human resources with workload and lack of clarity with regard to duties have maximum correlation with poor quality of care. Organizational structure and communication program categories gained the highest and lowest importance respectively. This information could be used by nursing managers and policy makers to plan programs in order to improve the quality of clinical nursing services.